Weisheitsschriften im "jüdisch-christlichen" Dialog an der Basis - Petschnigg, Edith 1978- (2014)
In the years following 1945, in response to the Shoah tragedy, a dialogue between Judaism and Christianity slowly emerged in Germany and Austria. Grass-roots dialogue initiatives represent particular expressions of the developing encounter. The Hebrew Bible and textual studies have often been at the core of this interfaith conversation. Texts from all parts of the biblical canon have been included. This article deals with the reception of the biblical Wisdom scriptures in “Jewish-Christian” dialogue, especially in the context of the “12th Austrian Christian-Jewish Bible Week”.
Keywords: Bible Study Weeks; Hebrew Bible; Jewish-Christian dialogue; Wisdom Texts